Optimization of production process activities in an effort to increase the production capacity of BZ 020 cover housing - Muhammad Syahrul Akmal; Orlanda Arya Hidayat; Moch Solikin (Universitas Negeri Yogyakarta, 2025)
The objectives of this study are: (1) To optimize the production process activities of Cover Housing BZ 020 production by implementing an 8-step improvement to increase production capacity. (2) To determine the comparison of the production capacity value of Cover Housing BZ 020 before and after the improvement. (3) To determine the activities that can be optimized to increase the production capacity of Cover Housing BZ 020 production. The method used in this research is the 8-step improvement research method approach. The data collection techniques used are (1) Observation and (2) Documentation. Meanwhile, the research instruments used are (1) Logbook, (2) Observation Sheet, and (3) Cellphone. The data analysis used is descriptive, comparing production capacity and operator activities. The results of this study indicate that: (1) Implementation of the 8-step improvement can be done at PT. Gemala Kempa Daya and is in accordance with the applicable standard SOP. (2) The results obtained after the improvement of production capacity are from 360 units/hour to 468 units/hour, or an increase of 30%. As a result of this improvement, the company also recorded a profit of IDR 55,800,000.00 per year. (3) By adding an extension conveyor, it can shorten the duration of two of the four operator work activities. The decrease in cycle time from 10 seconds to 8 seconds is due to optimizing work activities.